ChemInform Abstract: Highly Efficient Synthesis of Aryl and Heteroaryl Trifluoromethyl Ketones via o‐Iodobenzoic acid (IBX). Issue 47 (4th November 2013) - Cheng, Huicheng; Pei, Yu; Leng, Faqiang; Li, Jingya; Liang, Apeng; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract The coupling of aldehydes (I) and (V) with trimethyl(trifluoromethyl)silane (II) followed by deprotection of intermediate Tms‐protected alcohols affords trifluoromethylated alcohols (III) and (VI), which are readily oxidized with IBX to desired ketones (IV) and (VII) in high yields.